O Circuito SPCINE (2016-2018): uma análise da política cultural nas salas de exibição audiovisual da rede pública - Cucio, Bruno Gonçalves Simões (2020)
This master aims to study the activities of the Spcine Circuit project between the years of 2016 and 2018, making a critical analysis of the original objectives of the program and the history of the actions of the network of public audiovisual exhibition movie theaters. Exploring and relating the context of cultural policies in the city of São Paulo, the study seeks to situate the creation of the public company Spcine in 2014, describing the reasons that led public agents to develop the company. More specifically, it studies the Spcine Circuit, an unprecedented project with twenty public movie theaters spread across the city constituted by the company. The program offers an unified curatorship of movies that are shown to the public in free sessions or at low prices in order to establish a cultural policy that offers access to culture for the population of the city, in addition to providing screen space for Brazilian cinema, in particular from São Paulo city. Based on the numbers from all 20,000 sessions held by the program during the two-year and eight-month period and the exposure of testimonies by actors in the audiovisual sector and by Spcine members, this study lists the reasons why the network was founded and its first results.